Non-viral derivation of induced pluripotent stem cells from the canine umbilical cord - Atsushi Yamazaki; Seiji Shiozawa; Yuko Koushige; Hirotaka Kondo; Hisashi Shibuya; Kazuya Edamura (PLoS ONE, 2025)
In our previous study, canine induced pluripotent stem cells (iPSCs) were successfully generated from skin-derived fibroblasts, without the use of viral vectors. However, for clinical application of canine iPSCs in veterinary regenerative medicine, iPSCs generated from less invasive cell sources would be desirable. Therefore, the purpose of this study was to generate iPSCs from canine umbilical cords discarded at fetal birth. Canine umbilical cords were cut into small pieces and cultured in Dulbecco’s modified Eagle’s medium supplemented with 10% fetal bovine serum. Episomal vectors carrying 10 reprogramming gene sets were introduced into fibroblasts obtained from the umbilical cord using electroporation. When putative iPSCs colonies emerged, constitutive cell characterization was performed to evaluate cell morphology, proliferative potential, alkaline phosphatase staining, expression of stem cell markers, and the ability to differentiate into a trilineage following embryoid body and teratoma formation. Multiple putative iPSC colonies formed when reprogramming gene sets were introduced into fibroblasts obtained from the canine umbilical cord. The resulting colony cells stained positive for alkaline phosphatase, and showed expression of OCT4, SOX2, NANOG, SSEA1, and SSEA3 on fluorescent immunostaining for stem cell markers. Furthermore, the mRNA expression of canine endogenous OCT4 , SOX2 , and NANOG significantly increased, confirming the multi-differentiation potential of cells after embryoid and teratoma formation. In this study, iPSCs were successfully generated from canine umbilical cord without the use of a viral vector. Furthermore, canine umbilical cord-derived iPSCs were successfully cultured in a feeder-free manner. This study contributes to the development of veterinary regenerative medicine by using canine iPSCs.